Mental Health and Cognitive Outcomes in Older Adults After Disasters: Epidemiological Evidence, Determinants, Interventions, and Tiered Service Models for Policy and Education - Iswanto; Asri; Ratna Puji Priyanti; Fahruddin Kurdi; Maya Fitriasari (Al-Hijrah Indonesia, 2026)
Background: Natural and human-made disasters disproportionately increase the risk of mental health disorders and cognitive decline among older adults through trauma exposure, displacement, social isolation, and disrupted health services. Despite expanding literature, a synthesized evidence base linking epidemiology, determinants, interventions, and scalable service models for policy and educational use remains limited. Objective: This study aims to synthesize epidemiological evidence, identify key determinants, map effective interventions, and develop policy-ready tiered service models to support mental health and cognitive recovery in older adults following disasters. Methods: This narrative review, enhanced by evidence mapping, employs a bio-psychosocial framework aligned with the Inter-Agency Standing Committee (IASC) tiered MHPSS pyramid. Literature was retrieved from scientific databases (PubMed, Scopus, Web of Science), international clinical and policy guidelines (WHO, IASC, NICE, VA/DoD), and Indonesian context-specific sources. Data were narratively synthesized across epidemiological trends, risk/protective factors, intervention efficacy, and service pathway implementation. Results: Post-disaster epidemiological burden varies widely; meta-analyses of older earthquake survivors report pooled prevalences of 19.3% for PTSD, 23.5% for depression, and 10.9% for anxiety. Indonesian evidence (North Lombok) indicates 59.9% PTSD prevalence, strongly associated with chronic comorbidities (OR 2.49). Prospective Japanese cohorts demonstrate that severe housing damage accelerates cognitive decline, an effect moderated by social connectivity. Effective interventions include Psychological First Aid (PFA), task-sharing models (e.g., PM+), trauma-focused psychotherapy, cautious pharmacotherapy, and telehealth adaptations. Implementation requires age-friendly, tiered pathways with standardized screening and referral protocols. Conclusion: Post-disaster responses must integrate geriatric-sensitive, tiered MHPSS frameworks that ensure continuity of chronic care, preserve social networks, and establish clear, age-disaggregated monitoring systems. These findings provide a structured evidence base for emergency health policy, community response planning, and public health curriculum development.